Pemanfaatan Anchor Sebagai Platform Distribusi Podcast (Studi Kualitatif Podcast Notesa Nte Notutura) - Fitra Yani Mansyur (Connected: Jurnal Ilmu Komunikasi, 2021)
The presence of podcasts as new media which can be the choice of audio media allows anyone to become a good podcaster individually or in groups. The nature of the podcast offers freedom without the rules are binding like radio, making this profession quite attractive from various backgrounds, especially with the presence of Anchor as an application to create and distribute podcasts effectively. The research method used is qualitative. The technique of determining the amount of selected informants is by purposive sampling method. There are three (3) informants. Data collection methods used are observation, in-depth interviews and documentation. While the data analysis techniques used are data reduction, data presentation, and verification/conclusion. The results showed that the use of Anchor by Notesa Nte Noturura as podcast distribution platform, which aims to disseminate information in the form of podcast content to various platforms in order to increase audience reach and earn revenue through monetization. While the production process of Notesa Nte Notutura podcast goes through three (3) stages, the pre-production stage, production stage and post-production stage. In pre-production stage, the initial activity is determining the theme/topic and determining the interviewees through meetings with team members. Then at production stage, which is the vocal recording process using a microphone. The final stage is post-production, which is the audio editing and podcast distribution process through Anchor.